2013
DOI: 10.1073/pnas.1301430110
|View full text |Cite
|
Sign up to set email alerts
|

Responses of hair follicle–associated structures to loss of planar cell polarity signaling

Abstract: The mammalian hair follicle unit consists of a central follicle and a series of associated structures: sebaceous glands, arrector pili muscles, Merkel cells, and sensory nerve endings. The architecture of this multicellular structure is highly polarized with respect to the body axes. Previous work has implicated Frizzled6 (Fz6)-mediated planar cell polarity (PCP) signaling in the initial specification of hair follicle orientation. Here we investigate the origin of polarity information among structures within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…In Fz6 −/− mice, the anterior-posterior polarity of the Merkel cell cluster is lost and the Merkel cells are arranged in a complete circle (Chang and Nathans, 2013;Fig. 2B).…”
Section: Alleles For Ubiquitous Production Of Fz3 and Fz6mentioning
confidence: 99%
See 1 more Smart Citation
“…In Fz6 −/− mice, the anterior-posterior polarity of the Merkel cell cluster is lost and the Merkel cells are arranged in a complete circle (Chang and Nathans, 2013;Fig. 2B).…”
Section: Alleles For Ubiquitous Production Of Fz3 and Fz6mentioning
confidence: 99%
“…The procedures for preparation and processing of skin whole mounts for Merkel cells immunostaining and imaging of hair follicles based on melanin content are described by Chang and Nathans (2013) and Chang et al (2014).…”
Section: Skin Whole Mountsmentioning
confidence: 99%
“…Genetic studies identified the frizzled ( fz)/starry night (stan) pathway as an essential regulator of PCP in a number of Drosophila tissues/body regions, such as the wing, eye and abdomen (Adler, 1992;Gho and Schweisguth, 1998;Gubb and Garcia-Bellido, 1982;Held et al, 1986;Lawrence et al, 2004;Vinson and Adler, 1987;Wong and Adler, 1993;Zheng et al, 1995). This pathway also plays a key role in PCP in a variety of vertebrate tissues (and processes), such as the inner ear (Ezan and Montcouquiol, 2013;Montcouquiol et al, 2003;Wang et al, 2005), murine fur (Chang and Nathans, 2013;Wang et al, 2006;Wang and Nathans, 2007), murine respiratory system (Vladar et al, 2012) and mediolateral cell polarization and convergent extension during vertebrate embryogenesis (Goto and Keller, 2002;Heisenberg et al, 2000;Jessen et al, 2002;Tada and Smith, 2000;Wallingford et al, 2001). A second key regulator of PCP is the dachsous/fat pathway Casal et al, 2006;Harumoto et al, 2010;Ma et al, 2003;Matis and Axelrod, 2013;Merkel et al, 2014;Olofsson et al, 2014;Yang et al, 2002), which interacts with the fz/stan pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This tissue planar cell polarity (PCP) is dramatic in the cuticle of insects such as Drosophila, which is decorated with arrays of hairs and sensory bristles. Tissue polarity in Drosophila is under the control of the frizzled ( fz ) /starry night ( stan ) signaling pathway and in recent years it has become clear that this conserved pathway also controls planar polarity in many aspects of vertebrate development (Goodrich and Strutt, 2011; Wang and Nathans, 2007) including cell and tissue movements during gastrulation (Goto and Keller, 2002; Jessen et al, 2002; Takeuchi et al, 2003; Wallingford et al., 2001), the differentiation of stereocilia in the inner ear (Montcouquiol et al, 2003; Wang et al, 2005; Wang et al, 2006), the morphogenesis of the fur of mice(Chang and Nathans, 2013), kidney development (Babayeva et al., 2013; Goggolidou, 2013) and the polarity of the cilia in the respiratory epithelium (Vladar et al, 2012). …”
Section: Introductionmentioning
confidence: 99%